Evaluation of the scientific attitude in basic education students. Comparative study in state educational institutions In times of pandemic. - Berrocal Villegas, Carmen Rosa (2021)
The main objective of its was to evaluate the development of scientific attitude according to the perception of basic education students, in public educational institutions in lockdown. The study carried out corresponds to a quantitative methodological approach, descriptive level, non-experimental, cross-sectional, comparative design. The study sample consisted of 555 students, of which 195 belonged to the third year of secondary school, 148 to the fourth year of secondary school and 212 to the fifth year of secondary school.For data collection, a scale designed online and distributed through from whatsapp. The processing and analysis of the results show that there is a deficient development of the scientific attitude, in addition there are no significant differences in the level of development of the scientific attitude, according to the degree of studies, chronological age and gender.